2013
DOI: 10.1136/vr.100969
|View full text |Cite
|
Sign up to set email alerts
|

Bovine tuberculosis trends in the UK and the Republic of Ireland, 1995–2010

Abstract: Selected demographic features and trends in bovine tuberculosis (BTB) from 1995 to 2010 are described for the countries of the UK and the Republic of Ireland, using standardised definitions and measures. All countries experienced a reduction in the number of cattle and herds and in the proportion of dairy herds, while average herd size increased. In general, the trends indicate a stable situation of very low BTB prevalence in Scotland and, over most of the period, a rising prevalence in England and Wales. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 30 publications
4
114
0
Order By: Relevance
“…Clegg et al (2015a) found evidence of improvement in testing effectiveness among private veterinary practitioners in 2011 compared with 2008 in a range of indices, which is likely attributable to programme quality control (Duignan et al, 2012). Herd recurrence remains problematic, with approximately 12% positive at the post-derestriction test (Abernethy et al, 2013). Nonetheless, there has been clear evidence of improvement, with 2008-derestricted herds being 0.74 times (95% confidence interval: 0.68-0.81) as likely to be restricted in the 3 years following derestriction compared with 1998-derestricted herds (Gallagher et al, 2013).…”
Section: Evaluating National Progressmentioning
confidence: 94%
See 1 more Smart Citation
“…Clegg et al (2015a) found evidence of improvement in testing effectiveness among private veterinary practitioners in 2011 compared with 2008 in a range of indices, which is likely attributable to programme quality control (Duignan et al, 2012). Herd recurrence remains problematic, with approximately 12% positive at the post-derestriction test (Abernethy et al, 2013). Nonetheless, there has been clear evidence of improvement, with 2008-derestricted herds being 0.74 times (95% confidence interval: 0.68-0.81) as likely to be restricted in the 3 years following derestriction compared with 1998-derestricted herds (Gallagher et al, 2013).…”
Section: Evaluating National Progressmentioning
confidence: 94%
“…The latter is particularly important in Ireland: up to 36% of bTB breakdowns between 1995 and 2010 were first detected using this method (Abernethy et al, 2013). In approximately 80% of these breakdowns, no further reactors are detected at a full herd retest (the factory lesion test, FLT) (Olea-Popelka et al, 2008).…”
Section: The Importance Of Residual Infection In Btb Persistencementioning
confidence: 98%
“…How these factors may interplay to determine the risk of outbreaks in the specific case of bTB has been well documented in the UK and Ireland, where the rising incidence of the infection in the last 20 years has caused significant economic losses (Abernethy et al, 2013;Reynolds, 2006). The direct costs of bTB for UK taxpayers in 2009 were estimated in around £63M (about 95M USD) and over 25,000 cattle were culled (Johnston et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Despite increasing efforts and controls to slow the spread of bovine tuberculosis (bTB), the area affected by endemic bTB in England and Wales continues to expand (Broughan, Harris et al 2015) though the increasing trend in the incidence of bTB in England (Abernethy, Upton et al 2013) is not uniform. The lack of uniformity has been recognised by Defra who have divided England into three distinct spatial units, each associated with different disease management strategies, in an attempt to stem the east-and northward spread of bTB.…”
Section: Introductionmentioning
confidence: 99%